Exploring wicked problems of coal price fluctuations on indonesia's economic sector: a system thinking approch - Renna Ertanti, Susanna; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2018)
Abstract . Substances related to coal mining management have always been a sensitive issue for stakeholders. Including when the issue of domestic coal pricing, it again became wicked problems for the government. This means that the steps governments have and will take to address this issue have the potential to bring both positive and negative effects together for all concerned. Coal prices become important to be managed properly, considering that coal is still one of the energy sources used in power plants, which in fact the community needs its utilization. Therefore, it is important to know the variables that are affected by coal price fluctuations. Causal diagram, with its feedback system, can be one of the tools to find solutions for future regulation designing on the price of coal. From the result of interrelation analysis of the variables modeled in the causal loop diagram, it can be concluded that the fluctuation of coal price has direct impact on coal royalty and coal mining investment, and an indirect impact on state revenue. As for the electricity subsidy, as long as there is government intervention in certain policy form, the effect of coal price fluctuation is not very significant. However, GDP obviously gives effect to national electricity consumption. Causes of potential problems in the future due to coal price fluctuations are the decline in coal prices (as well as coal production) causing two potential problems: the decrease in state revenues and investment in the coal mining subsector. Some actions, both preventive and contingent, are detailed in a potential problem analysis method popularized by Kepner-Tregoe, which includes government appeals to coal mining companies to optimize stripping ratios and heavy equipment reconditions, incentives for production contributions, eliminating export duties, as well as policies on the use of shared facilities.Keywords: coal price, systems thinking, wicked problem, electricity subsidy, coal royalty, causal loop diagram, potential problem analysis